Shahamin Faizul Kung Bin Abdullah Lwn Asma Bte Haji Junus: Suatu Kritikan - Abdullah, Nor Aini (Journal of Malaysian and Comparative Law, 1991)
Shahamin Faizul Kung Bin Abdullah Lwn Asma Bte Haji Junus: Suatu Kritikan